Triclosan exposure and in vitro fertilization treatment outcomes in women undergoing in vitro fertilization - Radwan, Paweł (Environ Sci Pollut Res Int, 2020)
Triclosan (TCS) is a widespread environmental endocrine-disrupting chemical. Animal and in vitro studies suggested that triclosan may affect homesostasis of sex and thyroid hormones and impact on reproduction. Due to limited data derived from human epidemiological studies, this study was performed to examine the association between urinary concentration of triclosan and in vitro reproductive outcomes (methaphase II (MII) oocyte yield, top quality embryo, fertilization rate, implantation rate, and clinical pregnancy) among women from infertility clinic. The study participants were enrolled in an Infertility Center in Poland. A total of 450 women aged 25–45 (n = 674 IVF cycles) provided urine samples. The urinary concentrations of triclosan were evaluated using validated gas chromatography ion-tap mass spectrometry method. Clinical outcomes of IVF treatment were abstracted from patients electronic chart records. Triclosan was detected in urine of 82% of women with geometric mean 2.56 ± 6.13 ng/mL. Urinary concentrations of triclosan were associated with decrease implantation rate (p = 0.03). There were no association between other examined IVF outcomes: MII oocytes, embryo quality, fertilization rate, and exposure to triclosan. As this is one of the first study on this topic, studies among larger and more diverse population are needed to confirm the results.